Reference Governor Strategies for Vehicle Rollover Avoidance - R. A. G. Bencatel (2017)
This paper addresses the problem of vehicle rollover avoidance using reference governors (RGs) applied to modify the driver steering input in vehicles with an active steering system. Several RG designs are presented and tested with a detailed nonlinear simulation model. The vehicle dynamics are highly nonlinear for large steering angles, including the conditions where the vehicle approaches a rollover onset, which necessitates RG design changes. Simulation results show that RG designs are effective in avoiding rollover. The results also demonstrate that the controllers are not overly conservative, adjusting the driver steering input only for very high steering angles. IEEE